The effects of context and characteristics of women entrepreneurs on innovation performance - María Eulalia Chávez-Rivera; Jenny María Ruíz-Jiménez; María Mar del Fuentes-Fuentes (BRQ Business Research Quarterly, 2024)
Drawing on institutional and upper echelons theories, this study delves into the underexplored intersection of gender, context, and innovation performance among women entrepreneurs in Ecuador. Based on a sample of 45 women entrepreneurs, the study employs a fuzzy-set qualitative comparative analysis (fsQCA) and identifies six distinct paths to innovation performance. Contrary to initial expectations, our research findings substantiate that both institutional and social factors play a key role in fostering innovation in women-led firms in Ecuador. This innovation is facilitated by establishing close and frequent interpersonal connections, as well as by the age of the female entrepreneurs. Conversely, certain individual variables traditionally associated with innovation, such as education level or prior experience, manifest only sporadically. Our research enriches the discourse in gender and innovation studies by employing a multilevel approach and provides valuable insights into female entrepreneurial leadership's contribution to advancing developing economies.
Keywords: O32; J16; 650; Context; entrepreneurship; women; innovation performance